Evaluation the salinity of the Agricultural soils and unconfined Groundwater in the 7th Sector of the Lower Euphrates Basin-Syria - YAZBEK, Ibrahim (Latakia University Journal -Engineering Sciences Series, 2019)
The Seventh sector is located on the right bank of the Euphrates River at the town of ALbu- Kamal, the Syrian-Iraq border. Invest most heavily sector too, by planting different crops which irrigated by irrigation networks consisting of canals and earthen trenches. Research aims to evaluate the salinity of agricultural soils and unconfined groundwater by doing field surveying of agricultural soils of horizons from ground surface till depth 200cm. and making detailed chemical analysis of free groundwater and evaluate the quality of it to determine the salinity regions and the salinity degree. The salinity of agricultural soils of the sector are sulfate-chlorine and little degree chlorine - sulfate and chlorine classified non salinity –little salinity and little degree moderate salinity to very highly and highly salinity. The salinity of free groundwater between 1.3-28.5 g/l. and classified chlorine sulfate-magnesia calcic and sometimes sulfate chlorine- calcic magnesia. The research recommend to study and determine the leachingrequirement of salinity regions from actual test or choosing the most appropriate experimental equations. يقع القطاع السابع على الضفة اليمنى لنهر الفرات عند مدينة البوكمال على الحدود السورية – العراقية. وتُستثمَر معظم أراضيه بشكل كثيف بزراعة المحاصيل المختلفة، التي تروى بوساطة شبكات الري المؤلفة من أقنية وأخاديد ترابية. يهدف البحث إلى تقييم ملوحة الترب الزراعية والمياه الجوفية الحرة، عن طريق إجراء مسوحات حقلية للترب الزراعية بآفاق تبدأ من سطح الأرض حتى عمق 200سم، وإجراء التحاليل الكيميائية التفصلية للمياه الحرة وتقييم نوعيتها. وذلك بغرض تحديد المناطق المتملحة ودرجة ملوحتها. تمتاز ملوحة التربة الزراعية في القطاع السابع بأنها سلفاتية - كلوريدية وبدرجة أقل كلوريدية -سلفاتية وكلوريدية، تصنّف بأنها غير متملحة – قليلة التملح، وبدرجة أقل متوسطة الملوحة إلى شديدة التملح جداً وشديدة التملح. وتتراوح ملوحة المياه الجوفية الحرة بين 1,3 – 28,5 غرام/ليتر. وتصنّف بأنها كلوريدية سلفاتية – مغنيزية كلسية، وقد تكون أحياناً سلفاتية كلوريدية – كلسية مغنيزية. يوصي البحث بدراسة وتحديد احتياجات الغسيل للمناطق المتملحة، إما من واقع التجربة الفعلية أو اختيار أنسب المعادلات التجريبية.